Association between serum vitamin D and severe headache or migraine: A population-based analysis. - Shunfa Hao; Renyi Qian; Yiru Chen; Jingfang Liu; Xiaoyan Xu; Yunxiang Guan (PLoS ONE)
Background Vitamin D is thought to play a role in the development of migraine, but the nature of the relationship is still not fully understood. Although some studies have shown an association between vitamin D deficiency and migraine, other studies have had inconsistent or inconclusive results. Therefore, further research is needed to better understand the relationship between vitamin D and migraine headaches. Methods We selected 9142 participants from the 2001-2004 National Health and Nutrition Examination Survey (NHANES). In our study, the term "serum vitamin D" refers to the concentration of 25OHD2 + 25OHD3 (nmol/L) in the blood. Migraine was assessed based on self-reports in the miscellaneous pain section of the NHANES questionnaire. Associations between vitamin D and the risk of migraine were examined using multiple logistic regression, smoothed curve fitting, and stratified analyses. Results In our study, 20.53% of the participants suffered from migraine. The prevalence of migraine was higher in those with lower serum vitamin D levels. Participants in the highest quartile of serum vitamin D levels were found to have a 16% lower prevalence than those in the lowest quartile in the fully adjusted model (OR = 0.84, 95% CI 0.71-0.99). This result was supported by stratified analysis and smoothed curve fitting. Conclusion Our study showed a significant negative correlation between serum vitamin D levels and the prevalence of migraine in American adults.